SPADA Implementation on English E-Learning Course: Mechanical Engineering Students’ Perspectives - Tutut Nani Prihatmi; Maria Istiqoma (STAI Miftahul Ula Nganjuk, 2021)
This study investigates the Mechanical Engineering students’ perspectives on their E-learning experience using SPADA as the primary platform in learning English, including understanding its features and material delivered, difficulties during the learning process, and suggestions to improve the quality of learning English through SPADA ITN Malang. As the Indonesian government requires every school and institution to begin implementing E-learning, starting from March 2020, in the National Institute of Technology (ITN) Malang, all learning activities that have been performed conventionally converted into virtual learning using the web-based learning management system named SPADA ITN Malang. The findings show that SPADA ITN Malang has positive appraisal by the students in accessibility, comprehension, and satisfaction aspect. However, the difficulties found, which were internet connection and the lack of understanding of the material, should be addressed with suitable learning strategies to create a better English learning environment for the non-English department students.